PENGUATAN BISNIS PRODUK MAKANAN TRADISIONAL JOJORONG BERBASIS SOCIAL MEDIA MARKETING DI KABUPATEN SERANG - Arianto, Bambang; Oktaviani, Tita; Adi, Akhmad Eko (Dharma: Jurnal Pengabdian Masyarakat, 2023)
The development of Micro, Small and Medium Enterprises (MSMEs) for Jojorong traditional food has significant potential for strengthening the economic fundamentals of the Banten region. Nevertheless, the majority of Kebantenan culinary MSMEs still encounter various obstacles in business development, especially from the marketing aspect. The digital era of social media marketing (social media marketing) has become the main pillar for culinary MSMEs to expand market coverage by strengthening marketing aspects. In community service in Kadubeuruem Village, Serang Regency which was held on 10th June 2023, assistance was given to the strategy of strengthening the MSME business for traditional Jojorong food through the use of social media as a social media marketing channel. In this assistance, knowledge is provided about techniques for using social media marketing to expand the scope of the original Banten culinary market. The success of this activity can be seen from the Jojorong MSME owners who can take advantage of social media marketing as the best channel to introduce Jojorong traditional food globally. From the results of this activity it is known that strengthening business through social media marketing is the best means of developing Jojorong culinary MSMEs in Kadubeureum Village, Serang Regency.